Association of prior tuberculosis with altered cardiometabolic profiles of people with HIV: A comparative cross-sectional study in Uganda - Joseph Baruch Baluku; Diana Karungi; Brenda Namanda; Sharon Namiiro; Shamim Katusabe; Angut Mary Madalen; Martin Nabwana; Ronald Olum; Felix Bongomin; Edwin Nuwagira; Grace Kansiime; Christian Kraef; et al. (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: Cardiovascular disease (CVD) is the leading cause of mortality among people with HIV (PWH), but the influence of co-infections like tuberculosis (TB) on CVD risk remains underexplored. We aimed to compare cardiometabolic profiles of PWH with and without prior TB to determine if prior TB is associated with distinct cardiometabolic profiles. Methods: We conducted a comparative, cross-sectional study at a tertiary hospital in Kampala, Uganda. Participants were randomly sampled PWH aged ≥ 18 years on antiretroviral therapy. Specifically, we enrolled PWH with and without prior active TB (ratio of 1:1). Anthropometric measurements, blood pressure, fasting blood glucose (FBG), lipid profile, and glycated hemoglobin were assessed. Results: A total of 396 participants were enrolled (196 TB survivors and 200 controls). TB survivors had higher median FBG (5.5 vs. 5.1 mmol/l, p < 0.001) and a higher prevalence of DM (17.9 % vs. 9.5 %, p = 0.015). However, they had lower body mass index (23.0 vs. 25.1 kg/m2, p < 0.001) and waist circumference (81.0 vs. 84.0 cm, p = 0.026). TB survivors had higher HDL-c levels (1.0 vs. 0.8 mmol/l, p < 0.001), lower LDL-c levels (2.7 vs. 3.1 mmol/l, p < 0.001) and lower prevalence of dyslipidemia (81.7 % vs. 96.5 %, p < 0.001). Prior TB was independently associated with higher prevalence of elevated FBG (adjusted prevalence ratio (aPR) 1.79, 95 % CI 1.10–2.92) and DM (aPR 2.34, 95 % CI 1.11–4.94), but decreased risk of obesity (aPR 0.42, 95 % CI 0.20–0.88). Conclusion: TB survivors with HIV exhibit a higher risk of DM but lower risk of obesity compared to those without a history of TB, indicating a need for blood glucose monitoring among TB survivors.